In-vitro evaluation and in-silico studies applied on newly synthesized amide derivatives of N-phthaloylglycine as Butyrylcholinesterase (BChE) inhibitors. (June 2018) - Begum, Samreen; Nizami, Shaikh Sirajuddin; Mahmood, Uzma; Masood, Summyia; Iftikhar, Sahar; Saied, Summayya
Graphical abstract: Highlights: Schotten Baumann reaction conditions used to synthesize amide derivatives of N- phthalylglycine. Synthesized amide derivatives of N -phthaloylglycine (4a–4d) were evaluated for their Butyrylcholinesterase inhibition. The results of in silico evaluation were found to be comparable with the experimental results. The results suggest that the most potent molecule can be evaluated for in vivo activity and might be valuable for the drug discovery. Abstract: Amide derivatives of N- phthaloylglycine were synthesized under Schotten Baumann reaction condition. The structures of synthesized compounds (4a–d) were characterized by using FTIR, 1 HNMR and EI-MS. The compounds were evaluated for their in-vitro Butyrylcholinesterase inhibition and all of them exhibited good activity against this enzyme. Compound 4a ( IC50  = 6.5 ± 0.1) was found to be most potent compared with the reference compound Galantamine (IC50  = 6.6 ± 0.00038) and the other compounds (4b, 4c, 4d) were also possess that activity and hence can be employed for the discovery of lead compounds against Alzheimer's disease. The depth analysis of the binding mechanism of these newly synthesized compounds inside the binding gorge of BChE, an in silico technique, molecular docking was performed. All the compounds were found to be well accommodated within the binding pocket of BChE. Compounds 4a, 4b and 4c showed hydrogen bonding interaction with binding site residue TYR332. Moreover, hydrophobic and π–π interaction assisted the compounds to attain their enzyme inhibitory activity. These theoretical studies showed significant correlation with experimental results.